Julia [videorecording (DVD)] - Raschke-Robinson, Claudia; Portman, Rachel; Child, Julia (Sony Pictures, 2022)
The film brings to life the legendary cookbook author and television superstar who changed the way Americans think about food, television, and even about women. Using never-before-seen archival footage, personal photos, first-person narratives, and cutting-edge, mouth-watering food cinematography, the film traces Julia Child's twelve year struggle to create and publish the revolutionary Mastering the Art of French Cooking (1961) which has sold more than 2.5 million copies to date, and her rapid ascent to become the country's most unlikely television star. It's the empowering story of a woman who found her purpose, and her fame, at 50, and took America along on the whole delicious journey.